Principal Management In Developing Teacher Professionalism In State Junior High School Pidie District - Darmawati, Darmawati; Yanti, Hera; Iskandar, Iskandar (Journal of Educational Sciences, 2025)
This qualitative study analyzes the role, strategies, and stages of principals in developing teacher professionalism in State Junior High Schools in Pidie Regency. The research focuses on three key aspects: The principal's role in fostering the integrity of teacher professionalism, The principal's strategy in cultivating teacher teaching competence, and The principal's stages in developing teacher communication soft skills. Using a case study design, data was collected through observation, interviews, and documentation from principals and 14 certified teachers from State Junior High School 1 Muara Tiga and State Junior High School 3 Muara Tiga. The findings indicate that the principal's role involves value-based leadership, collecting accurate information, and effective communication. Implemented strategies include creating a conducive work environment, providing resources, building a collaborative culture, utilizing technology, and conducting periodic evaluations. The stages for developing communication soft skills involve planning, teacher professional development, supervision, evaluation, and data-driven decision-making.